1999
DOI: 10.1002/(sici)1096-9071(199902)57:2<169::aid-jmv14>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of human parvovirus B19 in Taiwan

Abstract: In order to determine the prevalence and risk factors of human parvovirus B19 (B19) infection in Taiwan, a seroepidemiological study was carried out in 19 townships. Serum samples were collected from 862 healthy residents, who were selected by stratified random sampling from various study areas. They were chosen from four different ethnic groups including aborigines, Fukien Taiwanese, Hakka Taiwanese, and mainland Chinese. Serum samples were screened for B19 IgG antibody by indirect antibody capture enzyme-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…The seroprevalence of B19 IgG antibody varies greatly by region and time of B19 epidemic 38,42 . In Taiwan the prevalence of anti‐B19 IgG and anti‐B19 IgM is 32.8 and 0.35%, respectively 43 . This result is similar to those observed in our study obtained from the donor population of the Chinese mainland.…”
Section: Discussionsupporting
confidence: 88%
“…The seroprevalence of B19 IgG antibody varies greatly by region and time of B19 epidemic 38,42 . In Taiwan the prevalence of anti‐B19 IgG and anti‐B19 IgM is 32.8 and 0.35%, respectively 43 . This result is similar to those observed in our study obtained from the donor population of the Chinese mainland.…”
Section: Discussionsupporting
confidence: 88%
“…We collected plasma samples from patients with various disease conditions and from blood donors, as well as from HIV‐positive drug users, to detect B19V antibodies and viral DNA. Our results showed that the overall B19V IgG antibody presence is between 21.9% and 41.8% in various populations in the greater metropolitan area of Hangzhou, East China, which is lower than the rate (∼60%) reported in adults worldwide [Nunoue et al, ; Anderson et al, ; Cohen and Buckley, ; Lim et al, ; Lin et al, ]. This result indicates that a large percentage of the population (∼60%) in this area has not been exposed to B19V, and thus individuals living in this area might be at a high risk of becoming infected with B19V.…”
Section: Discussionmentioning
confidence: 48%
“…Since the first discovery of B19V in 1974 [Heegaard and Brown, ], B19V infection has been reported worldwide [McOmish et al, ; Jordan et al, ; Aubin et al, ; Heegaard et al, ; Thomas et al, ]. The presence of B19V antibody ranges from ∼20% in young children to ∼80% in people >60 years [Nunoue et al, ; Anderson et al, ; Cohen and Buckley, ; Lim et al, ; Lin et al, ]. The presence of B19V DNA in healthy blood donors could be as high as 1% [Azzi et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between geographical regions and risk of RA detected in our study may be explained by the geographical variations in the prevalence of some possible environmental risk factors for RA, such as smoking42 and human parvovirus B19,43 in Taiwan.…”
Section: Discussionmentioning
confidence: 65%